The evolution of the Pharmacovigilance department in the pharmaceutical industry: results of an Italian national survey - Lisa Stagi; Ilenia Bocchi; Daniela Bernardini; Marika Ciappa; Stefania Dellon; Gian Nicola Castiglione; Silvia Romano; Eros Fabrizi; Amanda Mattavelli; Ilaria Grisoni; Gabriella Finizia; Stefano Bonato (SAGE Publishing, 2024)
Background: Pharmacovigilance (PV) is the science and activities relating to the detection, assessment, understanding, and prevention of adverse effects or any other medicine/vaccine-related problem. Since its inception in the 1960s, PV has undergone continuous evolution, progressing from a basic level mainly focused on the collection and analysis of cases in its earliest years to a complex system regulated by rigorous standards and laws with modern PV. In recent years, PV has faced the challenge of adapting to rapid scientific advancements, the complexity of the pharma industry, and the digital revolution. To better understand the current state and future developments of PV within pharma companies, the PV working group "Ernesto Montagna" of the Italian Society of Pharmaceutical Medicine (SIMeF ETS) conducted a national survey in Italy. Objectives: The main objective of this survey was to explore the current state and future developments of PV within Pharmaceutical Companies in Italy. Design: This study was designed as a national survey targeting members of the Italian Society of Pharmaceutical Medicine (SIMeF ETS). Methods: The survey utilized computer-assisted web interview (CAWI) technology to collect data from SIMeF members across affiliate and corporate companies, aiming to explore expectations for PV. A simplified version of the questionnaire was also sent to members of the Clinical Research and Medical Affairs (RICMA) and Real-World Evidence working groups of SIMeF to gather input from RICMA professionals regarding the role of PV in pharma companies. Results: The survey revealed that PV in pharma companies is undergoing a transformation, with the potential for greater strategic alignment with business objectives and stakeholder focus. However, there is still room for improvement, particularly in terms of perception within other company departments. It is evident that PV's evolution has only just begun. Conclusion: A critical factor in the evolution of PV is the adoption of a holistic and comprehensive approach to activities and processes. Scientific associations such as SIMeF can play a valuable role in cultivating new skills and capabilities among PV professionals, assisting, and supporting this change.